A beginner's guide to imaging in vivo tumour biochemistry. (11th September 2019) - Greenwood, Hannah; Edwards, Richard; Witney, Tim
Abstract : The Beginner's Guides are an ongoing series of feature articles in the magazine, each one covering a key technique and offering the scientifically literate but not necessarily expert audience a background briefing on the underlying science of a technique that is (or will be) widely used in molecular bioscience. The series will cover a mixture of techniques, including some that are well established amongst a subset of our readership but not necessarily familiar to those in different specialisms. This is a Beginner's Guide to imaging in vivo tumour biochemistry.